Language is a Means of Cognition and Communication for Teaching in Education - Mavjuda Makhmudovna, Nigmatova; Gulbakhor Davronovna, Niyazova; Dilbar Shonazarovna, Eshova; Dilfuza Shavkatovna, Mirzaeva (International Journal of Psychosocial Rehabilitation, 2020)
Cognitive linguistics characterizes a modern approach to language, language learning, and conceptual structure. Furthermore, it provides an outlook for language and the mind which is diametrically opposed to both Grammar and Formal Semantics. Cognitive linguistics investigates the relationship between human language, the mind, and socio-physical experience. The grammatical system determines the grammatical meaning of the words, grammatical categories and grammatical forms in the process of discourse. These following subsystems are conducted by different linguistic disciplines. The sound system is studied by phonology, the lexical meaning of words is studied by lexicology and grammatical meaning of words and sentence formations are studied by grammar. This article deals with the analysis of language cognition and communication for teaching in education.